Loneliness and depressive symptoms among men who have sex with men in China: A cross-sectional study - Liu, Yuhan; Yang, Yuting; Fu, Chaowei; Lin, Haijiang; Wang, Tingting; Wang, Shanling; Kuang, Jiawen; Chen, Xiaoxiao; Wang, Jingyi (Frontiers in Psychiatry, 2023)
Background: While psychosocial problems and their related factors in men who have sex with men (MSM) have been well documented in developed countries, there are still not many studies addressing this issue in China and the results are inconsistent. This study aimed to assess the prevalence of loneliness and depressive symptoms among MSM, examine their associated factors, and investigate potential factors moderating the link between depressive symptoms and loneliness. Methods: A cross-sectional study was conducted in Taizhou of Zhejiang Province in China between April and November 2021. Loneliness was assessed using the 3-item UCLA Loneliness Scale (UCLA-3), and depressive symptoms were measured using the Patient Health Questionaire-9 (PHQ-9). Data from 655 MSM were eligible for analysis. Logistic regression models were used to examine the associations between independent variables and the outcomes of loneliness and depression. The interaction terms were added in the models to assess the moderating effects. Results: Of the MSM sample, 13.28% and 7.48% perceived loneliness and reported moderate-to-severe depressive symptoms respectively. We found that participants who experienced loneliness were more likely to have younger age (OR 0.44, 95% CI 0.21, 0.93, 15-32 years as reference group), low social support (OR 3.60, 95% CI 2.14, 6.04), low self-esteem (OR 3.03, 95% CI 1.45, 6.32) and moderate-to-severe depressive symptoms (OR 5.45, 95% CI 2.66, 11.15). The participants with moderate-to-severe depressive symptoms were more likely to have low self-esteem (OR 6.78, 95% CI 3.08, 14.95) and feelings of loneliness (OR 5.51, 95% CI 2.66, 11.40). Stratified analyses showed that the magnitude of the associations between depressive symptoms and loneliness varied in MSM with different age, marital status, and self-esteem. Conclusions: Our study suggests that we need to pay attention to feelings of loneliness and depressive symptoms and their closely associated factors such as social support and self-esteem among MSM in China. The MSM who were young, not married, and had low self-esteem were especially vulnerable to the impact of depressive symptoms on loneliness.